60=-4(-9+x)

Simple and best practice solution for 60=-4(-9+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60=-4(-9+x) equation:


Simplifying
60 = -4(-9 + x)
60 = (-9 * -4 + x * -4)
60 = (36 + -4x)

Solving
60 = 36 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
60 + 4x = 36 + -4x + 4x

Combine like terms: -4x + 4x = 0
60 + 4x = 36 + 0
60 + 4x = 36

Add '-60' to each side of the equation.
60 + -60 + 4x = 36 + -60

Combine like terms: 60 + -60 = 0
0 + 4x = 36 + -60
4x = 36 + -60

Combine like terms: 36 + -60 = -24
4x = -24

Divide each side by '4'.
x = -6

Simplifying
x = -6

See similar equations:

| -200=4(6n-2) | | (8.5x)(2.25x)=3000 | | 8x+16=360 | | 25+6x=9x | | 2x+x=3000 | | 60=-4x-9+x | | -3x-4+6=2x+6+3x | | 8(3n+6)-20n-40= | | 2m=2[3(3+2m)-(3-m)] | | 7+3k=5k-3 | | 2(3x-4)=-(8-6x) | | -4a+5(-3a-3)=99 | | 7x^2-24x-21=-5 | | -9h-6+12h+40=12h | | Log[2](5x-3)=3 | | 2(-4-5p)+2p=-8(6p-5)+10(2+4p) | | 78=-7w+-13 | | 20p+7-11-p=-2(2p+4)-3(2p-2) | | 5ab=(b-1)*(4a+3) | | 6-2(x+4)=32 | | 4y^2-5y-30=0 | | 0.003x+1.2=0.15 | | 5.2+1.9x=2.9x | | 4x+17=112 | | 6(-3r+5)-5=115 | | 30x+x^2=10800 | | 20p+7-11-p=-2(2p+4) | | 5c+7a=116 | | 14x+21=0 | | 2x+6=4x+24 | | -6+(-6)x=-42 | | x+3/2=9/2 |

Equations solver categories